Pengaruh Tingkat Upah Terhadap Kinerja Pegawai Honorer Kabupaten Serdang Bedagai Dengan Kepuasan Kerja Sebagai Variabel Intervening - Syafrizal, Rodi; Saragih, Jopinus Ramli (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to determine the extent of the influence of wage behavior on the performance of honorary employees of Serdang Bedagai with job satisfaction as an intervening variable. This study uses a quantitative method approach with path analysis techniques. The results of this study indicate that the path analysis test shows that there is a direct influence of the wage level variable on the performance variable of 0.370. Meanwhile, the indirect effect through the job satisfaction variable is 0.410 x 0.549 = 0.225. From the calculation results obtained, the indirect effect through the job satisfaction variable is greater than the direct effect on the Y variable. variables eligible for intervention.